Identifying Plasmodium falciparum cytoadherence-linked asexual protein 3 (CLAG 3) sequences that specifically bind to C32 cells and erythrocytes (2005)
Adhesion of mature asexual stage Plasmodium falciparum parasite-infected erythrocytes (iRBC) to thevascular endothelium is a critical event in the pathology of Plasmodium falciparum malaria. It has beensuggested that the clag gene family is essential in cytoadherence to endothelial receptors. Primers used inPCR and RT-PCR assays allowed us to determine that the gene encoding CLAG 3 (GenBank accession no.NP_473155) is transcribed in the Plasmodium falciparum FCB2 strain. Western blot showed that antiseraproduced against polymerized synthetic peptides from this protein recognized a 142-kDa band in P. falci-parum schizont lysate. Seventy-one 20-amino-acid-long nonoverlapping peptides, spanning the CLAG 3(cytoadherence-linked asexual protein on chromosome 3) sequence were tested in C32 cell and erythrocytebinding assays. Twelve CLAG peptides specifically bound to C32 cells (which mainly express CD36) withhigh affinity, hereafter referred to as high-affinity binding peptides (HABPs). Five of them also bound toerythrocytes. HABP binding to C32 cells and erythrocytes was independent of peptide charge or peptidestructure. Affinity constants were between 100 nM and 800 nM. Cross-linking and SDS-PAGE analysisallowed two erythrocyte binding proteins of around 26 kDa and 59 kDa to be identified, while proteins ofaround 53 kDa were identified as possible receptor sites for C-32 cells. The HABPs’ role in Plasmodiumfalciparum invasion inhibition was determined. Such an approach analyzing various CLAG 3 regions mayelucidate their functions and may help in the search for new antigens important for developing antimalarialvaccines.